Lao People's Democratic Republic : Second Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2008)
This paper focuses on Second Poverty Reduction Strategy Paper for Lao People's Democratic Republic. The economic sectors have undergone significant restructuring. This restructuring has been concentrated on production capacities, quality and efficiency, thus contributing to economic growth and meeting the initial requirements for international integration. The government has also concentrated on the development of agricultural production to reorient the agriculture sector from semisubsistence and subsistence to commercial production to ensure the enhanced supply of raw materials to the processing industries, meeting the growing domestic requirements for agricultural products, and rapidly expanding agricultural exports.